Community of Faithful Dissidents. Representations of Anabaptism in Swiss Historical Fiction by Walter Laedrach and Katharina Zimmermann (Studia theodisca, 2016)
The twentieth-century Swiss local authors Walter Laedrach and Katharina Zimmermann rediscovered the dark chapter of Swiss history documenting the torture and execution of non-resistant and non-conformist Christians in the Bernese Oberland. The following analysis of the literary representation of these pacifist Anabaptists will identify historiographical sources that served as inspiration to the authors and the contributions their historical novels make in Switzerland’s process of coming to terms with its tragic past.